Mekanisme Kehilangan Tekanan dan Struktur Aliran Gas LPG pada Swivel Joint Style 40 dengan Sudut Gerak 45°: Studi Computational Fluid Dynamics - I Putu Redy Irawan; Atus Buku; Yusuf Siahaya (Infotekmesin, 2026)
Swivel joints are an important component in the loading arm system that affects the efficiency of LPG transfer; however, the characteristics of pressure distribution and flow patterns in a 40° style swivel joint with a rotation angle of 45° have not been widely studied. This study aims to analyze the pressure distribution and flow structure using the Computational Fluid Dynamics (CFD) method with the k–ω SST turbulence model. The simulation results show that the flow is in a turbulent regime with a Reynolds number of around 71000 and a Darcy friction factor of 0.035. The pressure distribution is in the range of −0.0293 to 0.0445 Pa, with the maximum pressure concentrated on the outer side of the bend due to the centrifugal effect, while the minimum pressure appears on the inner side of the elbow, which triggers the formation of secondary flow. Streamline visualization shows the formation of a low-intensity Dean vortex without a significant recirculation zone, with a maximum velocity of around 0.244 m/s. The novelty of this research lies in the integrated analysis of pressure distribution and flow structure in a 40° 45° swivel joint style configuration that represents the actual operating conditions of the loading arm. The research results provide a scientific basis for optimizing the swivel joint design to minimize pressure loss and improve the efficiency of the LPG transfer system.